New records of introduced species in the Mediterranean Sea (April 2023) - FORTIČ, ANA; AL-SHEIKH RASHEED, REEM; ALMAJID, ZOUHAIR; BADREDDINE, ALI; BÁEZ, JOSÉ CARLOS; BELMONTE-GALLEGOS, ANGEL; BETTOSO, NICOLA; BORME, DIEGO; CAMISA, FEDERICA; CARACCIOLO, DANIELA; ÇINAR, MELIH ERTAN; CROCETTA, FABIO; et al. (Mediterranean Marine Science, 2023)
This Collective article reports 17 introduced species and 22 new locations for these species in the Mediterranean Sea. The reports are from three different Marine Strategy Framework Directive (MSFD) subregions (Aegean-Levantine Sea, Adriatic Sea and Western Mediterranean Sea) and the Sea of Marmara and cover ten different countries. The goal of consistent and detailed reporting of introduced species is to complement the existing species inventories and serve as a basis for establishing monitoring strategies and other conservation measures. Some of the reports from this article are the first species records for the Mediterranean Sea, namely the green alga Udotea flabellum from the Aegean Sea (Turkey) and the deepbody boarfish Antigonia capros from the Balearic Sea (Spain). In addition, new records of introduced species are included for different seas, namely the moon crab Matuta victor for the Aegean Sea (Greece), the whale shark Rhincodon typus and the lionfish Pterois miles for the Alboran Sea (Spain), the almaco jack Seriola rivoliana for the Tyrrhenian Sea (Italy), and the hound needlefish Tylosurus crocodilus for the Adriatic Sea (Italy). Furthermore, reports on first country records are included: the red alga Colaconema codicola from Slovenia, the nudibranch Melibe viridis from Bosnia and Herzegovina, the lionfish Pterois miles from Montenegro, and the goldstripe sardinella Sardinella gibbosa from Syria, which also represents a second record for the Mediterranean Sea. Furthermore, the occurrence of the scleractinian coral Oculina patagonica was noted in Gulf of Lion (France). Four polychaete species, namely Leodice antennata, Timarete punctata and Branchiomma bairdi, are reported from the vermetid reef habitat and two of them (L. antennata and B. bairdi) are also recorded for the first time in Lebanon. Evidence for established populations of the Asian date mussel Arcuatula senhousia in the Sea of Marmara (Turkey) and the rayed pearl oyster Pinctada radiata around the island of Sardinia (Italy) is provided.